Results of demographic study - Kraus, J (Demosta, 1987)
The author summarizes the results of a 1985 nationwide survey of married women in Czechoslovakia. Findings are presented on number of children by age of woman and on realized and desired family size by age of woman. Comparisons are made with similar data for the years 1978 and 1981.
Keywords: Demographic Factors; Summary Report; Family Planning; vyspělé země; Comparative Studies; fertilita; Europe; Europe, Eastern; Czechoslovakia; Family Characteristics; Evropa; Family Size, Ideal; Family Size, Desired; Československo; Family And Household; služby plánování rodičovství; Fertility Measurements; Research; Population Characteristics; Developed Countries; charakteristiky rodiny; porodnost; parita; věkové faktory; východní Evropa; Family Planning Services; Demographic Surveys; Family Size; populace; Population Characteristics--women; populační dynamika; Demography; Fertility; demografie; Population; Age Factors; výzkum; populační charakteristiky; Birth Rate; Population Dynamics; Eastern Europe; Marital Fertility; Parity